EVALUATION OF ATRIAL CONTRACTILE FUNCTION DISORDERS AND FIBROSIS AS PREDICTORS OF CHRONIC HEART FAILURE - O. M. Drapkina; E. V. Cherkunova (Рациональная фармакотерапия в кардиологии, 2015)
Chronic heart failure (CHF) is a major health problem in many countries now, and the cost of hospitalization is high. Early detection of atrial dysfunction, relationships between onset of symptoms and dysfunction of the atria, as well as their role in the development of systolic and diastolic heart failure is important. Interest in the assessment of left atrial transthoracic echocardiography with calculation of left atrial function index (LAFI) fraction and assessment of myocardial fibrosis with special software packages takes place lately. The search for ways to develop non-invasive methods for determining the fraction of atrial fibrosis and dysfunction is now underway. Detection of the most sensitive and specific methods will help to diagnose the initial manifestation of CHF and find an individualized approach to the treatment of each patient.